2010
DOI: 10.1007/s11243-010-9334-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oxidation of d(+)melibiose and cellobiose by N-bromoacetamide using a rhodium(III) chloride catalyst

Abstract: The kinetics of oxidation of the sugars D(?)Melibiose (mel) and Cellobiose (cel) by N-bromoacetamide (NBA) in the presence of Rh(III) chloride as homogeneous catalyst in acidic medium at 45°C have been investigated. The reactions are first-order with respect to [NBA], [Rh(III)] and [substrate]. The rate is proportional to [H ? ]. No effects of [Hg(II)], [NHA] or [Cl -] on the rates were observed. Ionic strength and dielectric constant also have little effect. The observed kinetic data, available literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…N-bromoacetamide has been used as an oxidant in Ru(III) [5]-, Ir (III) [2]-and Pd(II) [15]-catalysed oxidation of reducing sugars in acidic medium. In each case, it has been observed that HOBr is the main reactive species of NBA.…”
Section: Discussion and Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…N-bromoacetamide has been used as an oxidant in Ru(III) [5]-, Ir (III) [2]-and Pd(II) [15]-catalysed oxidation of reducing sugars in acidic medium. In each case, it has been observed that HOBr is the main reactive species of NBA.…”
Section: Discussion and Mechanismmentioning
confidence: 99%
“…(3) The role of reducing sugar molecule in the presence of Pd(II) chloride as catalyst and NBA as an oxidant in acidic medium is similar to the reported role of reducing sugar in the presence of Ir(III)/Ru(III) chloride and NBA in acidic medium. (4) Pd(II) chloride in acidic medium participates in the reaction under investigation in the same way as it is reported in Ru(III) [5]-and Ir(III) [2]-catalyzed oxidation of reducing sugars by NBA in acidic medium. …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…2+ in Alkaline Medium: Spectrophotometric and Kinetic Studies of some simple reducing sugars have been studied using various transition metals like Cr(VI), Cu(II), Fe(III), Ir(III), Rh(III), Pd(II), Ru(III) [21][22][23][24][25][26]. The kinetics of oxidation of sugars has been the most popular and interesting research in recent years [27][28][29][30].…”
Section: Role Of Ru(iii) As Inhibitor In Oxidation Of Arabinose and Rmentioning
confidence: 99%
“…The dye is also important to pathologists [1]. Colored dye waste frequently contains a spectrum of metals and other toxic organic pollutants [2] including dyes and the presence of dye colors may indicate the existence of toxicants [3]. It is the disodium salt of benzene-azo-6:8-disulphuric acid and its molecular structure is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%